Language in the Classroom: Comparisons of Four Bilingual Environments - Alejandro Brice; Roanne Brice (South African Journal of Communication Disorders, 2000)
Enrolment of students from varying cultural and linguistic backgrounds has increased significantly over the last few years in the United States. One can therefore assume that the changing demographics also indicates the diverse home language and culture of students entering U. S. schools today. These students exhibit various levels of functioning within the context of the U.S. school culture; specifically, they are acculturating to the school culture and also learning English. Language proficiency and academic success are dependent upon the degree to which the teachers and speech-language pathologists are capable of meeting the learning needs of students in the classroom. Teachers and speech-language pathologists may be unaware of their teaching and therapy practices, particularly their use of language. The purpose of this article is to review three studies across four environments investigating teacher and therapist language involving bilingual students.